Role of Self-esteem on Career Determination of Grade Twelve Students: A Narrative Inquiry - Mishra, Somnath (NPRC Journal of Multidisciplinary Research, 2025)
This study explores the impact of self-esteem on career building. Recognizing the crucial nature of this life stage for career planning, the research investigates how a student's self-belief impacts their ability to choose a fulfilling career path. Through interview, the study gathers data from grade twelve students to assess their self-esteem and career aspirations. By analyzing this data, the research aims to identify key insights into the relationship between self-perception and career choices.The research aims to understand how individual levels of self-esteem, encompassing feelings of self-worth, confidence, and personal capability, influence their career aspirations, decision-making, and perseverance in pursuing specific vocational paths. Preliminary findings suggest a significant correlation between robust self-esteem and clarity in career goals, proactive exploration of opportunities, and resilience in facing challenges associated with career planning. Conversely, students exhibiting lower self-esteem often reported feelings of uncertainty, susceptibility to external pressures, and a tendency to limit their career choices.The findings explore that students with high self-esteem exhibit greater confidence and clarity in their career determination. Conversely, lower self-esteem might lead to indecisiveness or a tendency to limit career options. This research holds significant implications for policy makers, government organizations, adolescence education, school curriculum developers, educators and career counselors. By understanding the role of self-esteem, they can develop strategies to support students in building self-confidence and making well-informed career decisions for a successful future.